Reducing broadcasting route request packet through LF-AODC - Ismail Roswan, Zulkifli Che Zalina, Samsudin Khairulanuar, (Universiti Pendidikan Sultan Idris, 2017)
Reducing broadcasting route request packet through LF-AODC by Ismail Roswan, Zulkifli Che Zalina, Samsudin Khairulanuar,